Предмет: Алгебра,
автор: zuevelizaveta
Решите уравнение
х(2х-3)(х-6)=0
9х^2-1=0
х^3-16х=0
Пожалуйста
Ответы
Автор ответа:
0
х(2х-3)(х-6)=0;
x(2x^2-12x-3x+18)=0;
x=0;
2x^2-12x-3x+18=0
2x^2-15x+18=0
D=225-144=81=9^2
x1=15+9/4=6
x2=15-9/4=1,5
9х^2-1=0;
9x^2=1;
x^2=1/9
x=+_1/3
х^3-16х=0;
x(x^2-16)=0;
x=0;
x^2-16=0; x^2=16 => x=+_4
x(2x^2-12x-3x+18)=0;
x=0;
2x^2-12x-3x+18=0
2x^2-15x+18=0
D=225-144=81=9^2
x1=15+9/4=6
x2=15-9/4=1,5
9х^2-1=0;
9x^2=1;
x^2=1/9
x=+_1/3
х^3-16х=0;
x(x^2-16)=0;
x=0;
x^2-16=0; x^2=16 => x=+_4
Автор ответа:
0
Спасибо
Похожие вопросы
Предмет: Русский язык,
автор: Bogdana500
Предмет: История,
автор: buralovazina
Предмет: Русский язык,
автор: girgensonkarina
Предмет: Математика,
автор: semkin81
Предмет: Алгебра,
автор: имана95